Comparison of two methods for analysis of gene–environment interactions in longitudinal family data: the Framingham heart study - Sung, Yun Ju; Simino, Jeannette; Kume, Rezart; Basson, Jacob; Schwander, Karen; Rao, D C. (Frontiers in Genetics, 2014)
GxE interaction analysis can potentially enhance gene discovery for common complex traits. However, genome-wide interaction analysis (GWIS) is computationally intensive. Moreover, analysis of longitudinal data in families is much more challenging due to the two sources of correlations arising from longitudinal measurements and family relationships. GWIS of longitudinal family data can be a computational bottleneck. Therefore, we compared two methods for analysis of longitudinal family data: a methodologically sound but computationally demanding method using the Kronecker Model (KRC) and a computationally more forgiving method using the Hierarchical Linear Model (HLM). The KRC model uses a Kronecker product of an unstructured matrix for correlations among repeated measures (longitudinal) and a compound symmetry matrix for correlations within families at a given visit. The HLM uses an autoregressive covariance matrix for correlations among repeated measures and a random intercept for familial correlations. We compared the two methods using the longitudinal Framingham Heart Study (FHS) SHARe data. Specifically, we evaluated SNP-Alcohol (amount of alcohol consumption) interaction effects on HDL-cholesterol. Keeping the prohibitive computational burden of KRC in mind, we limited the analysis to chromosome 16, where preliminary cross-sectional analysis yielded some interesting results. Our first important finding was that the HLM provided very comparable results but was remarkably faster than the KRC, making HLM the method of choice. Our second finding was that longitudinal analysis provided smaller p values, thus leading to more significant results, than cross-sectional analysis. This was particularly pronounced in identifying GxE interactions. We conclude that longitudinal analysis of GxE interactions is more powerful and that the HLM method is an optimal method of choice as compared to the computationally (prohibitively) intensive KRC method.